The Role of Digital Literacy Education in Children's Learning Experiences at Cikareo Elementary School - Suci Soleha, Cita; Aris Gundara; Ariawan, Ariawan; Teguh Aji Saputra; Siti Sya’diah (ENGAGEMENT: Jurnal Pengabdian Masyarakat, 2026)
This study aims to understand how digital literacy education can help improve the learning experience of elementary school students at SDN Cikareo, a school in a rural area. This research was motivated by the limited technological facilities in rural schools and the lack of exposure of students to the use of digital technology in learning. Using a qualitative descriptive method, this study collected data through observation, interviews, and documentation studies. The digital literacy activities carried out included PowerPoint presentations, educational video screenings, Canva-based interactive quizzes, and drawing activities brought to life with artificial intelligence applications. The results showed positive responses from students, marked by increased motivation, enthusiasm, and active involvement in the learning process. These findings also revealed that digital literacy not only enriches the learning experience but also opens up new opportunities to develop students' interests and talents, such as animation and digital games. In conclusion, digital literacy education is a relevant learning strategy to overcome facility limitations in rural schools and equip students with 21st-century skills. This research contributes significantly to expanding access and optimizing the quality of education in remote areas.